MindPlay Virtual Reading Coach: Does It Affect Reading Fluency in Elementary School? - Kloos, Heidi; Sliemers, Stephanie; Cartwright, Macey; Mano, Quintino; Stage, Scott (Frontiers in Education, 2019)
Important strides have been made in the science of learning to read. Yet, many students still struggle to attain reading proficiency. This calls for sustained efforts to bridge theoretical insights with applied considerations about ideal pedagogy. The current study was designed to contribute to this conversation, namely by looking at the efficacy of an online reading program. The chosen reading program, referred to as MindPlay Virtual Reading Coach (MVRC), emphasizes the mastery of basic reading skills to support the development of reading fluency. Its focus on basic skills diverges from the goal of increasing reading motivation. And its focus on reading fluency, versus broad literacy achievement, offers an alternative to already existing reading enrichment. In order to test the efficacy of MVRC, we recruited three school districts. One district provided data from elementary schools that used the MVRC program in Grades 2 to 6 (N = 2,531 total). The other two districts participated in a quasi-experimental design: Six 2nd-grade classrooms and nine 4th-grade classrooms were randomly assigned to one of three conditions: (1) instruction as usual, (2) instruction with an alternative online reading program, and (3) instruction with MVRC. Complete data sets were available from 142 2nd-graders and 172 4th-graders. Three assessments from the MVRC screener were used: They assessed reading fluency, phonic skills, and listening vocabulary at two time points: before and after the intervention. Results show a clear advantage of MVRC on reading fluency, more so than on phonics or listening vocabulary. At the same time, teachers reported concerns with MVRC, highlighting the challenge with reading programs that emphasize basic-skills mastery over programs that seek to encourage reading.